ECONOMIC ANALYSIS OF MARKETING EFFICIENCY OF PINEAPPLE IN KANO STATE MARKETS, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2020)
The study analysed the marketing efficiency of pineapple in selected markets in Kano metropolis. Data was collected with the used of questionnaire and were analysed using descriptive statistics, market margin analysis and market efficiency. Results shows that the majority (33.3%) of the respondents were within the ages of 47-55 years, followed by 23.8% within the age range of 29-37 years and 9.5% of age range of 56-64 years were the minimum. Household size, in the wholesalerâ€™s side category 5-8 size had the highest members with 42.80%, followed by 1-4 and 17-20 with 19.10% each, while 14.30% had 9-12 and the least was households within the range of 13-16 with only 4.8%, while in the retailerâ€™s side category 1-5 size had the highest members with 40.90%, followed by 11-15 with 24.90%, then 22.60% had 6-10 while 9.10% had 16-20 size and the least was household within the range of 21-25 with only 2.30%. However, 31-37years category ranked the least with 4.80%. On the retailers side the result reveals that 13-20 years category ranked the highest with 41.00% and 37-44years category were the least with 6.80% each. The marketing margin analysis indicated that for every 14.4kg pineapple, gross marketing margin of wholesalers N 158.85 was higher than that of retailers N 129.66 whereas net marketing margin of retailers with N 91.24 was higher than that of wholesalers with  N 59.09, return on investment of retailers with 1.11 was also higher than that of wholesalers with 1.08, and however, marketing margin of wholesalers
Keywords: Analysis; Efficiency; Pineapple; Marketing; Kano State